'Embu' Wh- questions in Cypriot Greek: A comparative study. Issue 1 (12th August 2019) - Kanikli, Antri; Tsoulas, George
Abstract : This paper proposes a novel syntactic analysis for embu Wh- questions in Cypriot Greek; a Wh- question variant which is similar to the est-ce que interrogatives in French and the é que interrogatives in European Portuguese. The paper examines properties of the embu questions which have not been addressed in the literature and investigates the asymmetries these interrogatives are assumed to display. Adopting a Split-CP analysis, we argue that embu is a Wh- head; an analysis which accounts for the examined syntactic and semantic properties of these questions. Given the similarities of these structures to the é que interrogatives in European Portuguese and the est-ce que interrogatives in French, the paper reviews the disagreements in the literature with regards to the analysis of these Wh - questions and explores whether the analysis that is proposed for embu questions could accommodate these data as well.